Analysis of stress and kinematical and physiological demands during firefighters workday - Romero-Sánchez, J.; Gómez-Carmona, C.; Bastida-Castillo, A.; Pino-Ortega, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The work of firefighters is considered one of the professions with greater physical demands and predisposition to suffer stress, due to the hazardous working conditions and the responsibility with human lives. The aims of the present study were to: (i) describe the kinematical, physiological and stress demands of firefighters, and (ii) compare these demands in relation to the experience years. Eight firefighters from the fire department of Cartagena participated voluntarily, dividing them into two groups: (1) experienced: >12 years (n=4); (2) novels: <7 years (n=4). The registered variables were total acceleration (AcelT), heart rate average (HRavg) and sympathetic-parasympathetic ratio (R-S|Ps). The results shown differences between activities, finding the highest values in sport and exits. In the between-groups comparison, differences in AcelT and HRavg in sport (p<.05), being higher in experienced group; and differences in R-S|Ps in practice and exits with urgency (p<.05), being higher in novels group. In conclusion, the firefighters with less experience suffer greater stress during workday. Therefore, it is necessary the incorporation of qualified staff to design specific training and coping strategies before the resolution of conflicts adapted to the real situation.